Demographic variation and risk factors regarding breast cancer among female in Southern Punjab, Pakistan - Ahmad, Waheed; Firasat, Sabika; Akhtar, Muhammad Sohail; Afshan, Kiran; Jabeen, Kaukab; Amjad, Rubina Ali (Journal of the Pakistan Medical Association, 2021)
Objective: Breast cancer is a second major cause of female death worldwide. This study aimed to explore epidemiology, clinical profiles and contribution of reproductive and non-reproductive risk factors in breast cancer development among females from South Punjab, Pakistan. Methods: Data was collected through hospitals between October 2017 and March 2018 and study got approval by Bioethical Committee of Quaid-i-Azam University in September, 2017. A total of 163 cases and 163 age-matched controls were recruited through non-probability consecutive sampling method. All histologically confirmed patients irrespective of age, family history, clinical presentation and histopathological type were included in the study as cases. Patients, who were not willing to participate were excluded from the study. Details regarding socio-demographic characteristics, family history of cancer, reproductive health and lifestyle factors were recorded using a structured questionnaire. Conditional logistic regression was performed to calculate odds ratios at 95% confidence intervals for breast cancer by menstrual and reproductive factors after adjustment of potential confounders. Conditional logistic regression was also applied for various demographic and medical risk factors/exposures. Results: We found positive family history and hypertension significantly linked to an increased breast cancer risk (adjusted O.R >1.5, 95% CI, P<0.05) whereas, intense physical activity, increased anthropometric measurements and breastfeeding per child in months were inversely associated with breast cancer risk (adjusted O.R <1.0, 95% CI, P<0.05) in our study cohort. Conclusion: Our study reaffirms contribution of established risk factors for breast cancer, highlights protective factors and necessitates awareness/screening programs to reduce breast cancer burden in upcoming generations. Continuous...